The genus Paravelia Breddin, 1898 (Hemiptera: Heteroptera: Veliidae) in Brazil, with descriptions of eight new species - Rodrigues, Higor D.d.; Moreira, Felipe F.f.; Nieser, Nico; Chen, Ping Ping; Melo, Alan L.; Dias-Silva, Karina; Giehl, Nubia F.s. (Zootaxa, 2014)
Eight new species of Paravelia Breddin, 1898 from Brazil are described and illustrated: P. amapaensis sp. nov. from Amapá State, P. bipunctata sp. nov. from Minas Gerais, Mato Grosso and Mato Grosso do Sul States, P. bilobata sp. nov. and P. polhemusi sp. nov. from Mato Grosso State, P. bahiana sp. nov. from Bahia State, P. lacrymosa sp. nov. from Minas Gerais State, P. micromaculata sp. nov. from Maranhão State, and P. ornata sp. nov. from Amazonas State. The genus is redescribed, with photos of the dorsal view for nineteen species: P. basalis (Spinola), P. biae Spangler, P. boliviana Breddin, P. bullialata Polhemus & Polhemus, P. capillata (Drake& Harris), P. capixaba Moreira, Nessimian & Rúdio, P. conata (Hungerford), P. dilatata Polhemus & Polhemus, P. foveata Polhemus & Polhemus, P. itatiayana (Drake), P. lanemeloi Moreira & Barbosa, P. manausana Polhemus & Polhemus, P. nieseri Moreira & Barbosa, P. platensis (Berg), P. recens (Drake & Harris), P. rotundanotata (Hungerford), P. spinifera Polhemus & Polhemus, P. splendoris (Drake & Harris) and P. williamsi (Hungerford). Three of these species are recorded for the first time from Brazil: P. platensis, P. spinifera and P. williamsi. Also, the macropterous forms of P. capixaba and P. dilatata are described. Lastly, an identification key to the 36 species of Paravelia recorded from Brazil and a checklist of described species are presented.